Denitrifying microbial genes quantification attests inference for potential N2O emissions in sugarcane soils by enzymatic bioanalysis - de Oliveira, Luciano Ricardo; Kozusny-Andreani, Dora Inés; Monteiro, Gabriel Gustavo Tavares Nunes; Mendes, Ieda de Carvalho; Rossetto, Raffaella; Vanzela, Luiz Sergio; Vazquez, Gisele Herbst; Navarrete, Acacio Aparecido (Frontiers in Soil Science, 2024)
This study evaluated the relationships and sensitivity of denitrifying microbial gene abundance, as well as the activities of soil enzymes β-glucosidase (GLU) and arylsulfatase (ARYL), to assess the quality of sugarcane soils managed with vinasse (V), filter cake (FC), and mineral fertilizer (MF). Composite soil samples were collected using a systematic sampling approach that included two soil classes (Ferralsol and Acrisol), two textures (clayey and sandy), three management systems (V, V+FC, and MF), two sampling seasons (rainy and dry), and three replicates, totaling 72 samples. Analysis of soil organic carbon (SOC), and macro- and micronutrients differentiated the Ferralsol and Acrisol samples into distinct groups based on agricultural management (Global R = 0.554) and showed some overlap based on soil texture (Global R = 0.369). The number of nirK, nirS, and nosZ I gene copies per gram of soil, determined by Real-Time Quantitative PCR (qPCR) based on genomic DNA isolated from the 72 soil samples, was higher in the rainy season compared to the dry season (P<0.05). None of the genes evaluated revealed a consistent response to different sugarcane soil managements, showing specific response patterns for each soil class and texture. In the Ferralsol, the activities of GLU and ARYL increased in the following order: V < MF < V+FC, regardless of soil texture (sandy or clayey) and sampling season. The average activity of the two enzymes in both V+FC and MF treatments was 1.8 times higher in sandy soil and 3.9 times higher in clayey soil compared to soil managed with vinasse. In the Acrisol, no significant differences among the treatments were observed. Statistical analyses revealed negative correlations (P<0.05) between the number of copies of the nirK and nosZ I genes and GLU and ARYL activities in the soil during both seasonal periods analyzed. The number of copies of these two microbial genes was also negatively correlated with the soil organic matter in the rainy season. Thus, the indications of sugarcane soil quality based on enzymatic analyses were corroborated by the lower abundance of genes associated with denitrification process. The findings of this study open the possibilities to infer about the potential for N2O emission from these sugarcane soils based on GLU and ARYL activities.